2011
DOI: 10.1007/s11256-011-0177-y
|View full text |Cite
|
Sign up to set email alerts
|

The Rhetoric of Care: Preservice Teacher Discourses that Depoliticize, Deflect, and Deceive

Abstract: How teachers ''care'' for students is a well-established line of inquiry in educational research, but the ways such ''care'' may function as symbolic violence have received scant attention. In this ethnographic investigation of classroom disciplinary interactions, the characteristics and functions of preservice teachers' care discourses are examined. By translating deficit discourses into expressions of praise for students' nonacademic talents, the participants' rhetoric of care effectively shifts blame for fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…These horizontal relationships place teachers as facilitators or partners in helping students work together to achieve shared goals (Ancess, 2003;AntropGonzález & De Jesús, 2006;Johnson, 2009). This is in contrast to hierarchical power relations in which the carer "may decide what those best interests are without listening to the expressed needs of the cared-for" (Noddings, 2005, p. xv), or a savior or colonialist mentality in which teachers, holding deficit views of students and the communities they come from, believe they have to "save" students from what they perceive to be uncaring family or community environments (Beauboeuf-Lafontant, 2002;Rolón-Dow, 2005;Toshalis, 2012).…”
Section: Hard Carementioning
confidence: 99%
See 2 more Smart Citations
“…These horizontal relationships place teachers as facilitators or partners in helping students work together to achieve shared goals (Ancess, 2003;AntropGonzález & De Jesús, 2006;Johnson, 2009). This is in contrast to hierarchical power relations in which the carer "may decide what those best interests are without listening to the expressed needs of the cared-for" (Noddings, 2005, p. xv), or a savior or colonialist mentality in which teachers, holding deficit views of students and the communities they come from, believe they have to "save" students from what they perceive to be uncaring family or community environments (Beauboeuf-Lafontant, 2002;Rolón-Dow, 2005;Toshalis, 2012).…”
Section: Hard Carementioning
confidence: 99%
“…Sympathetic or "soft caring" teachers who take pity on students' social circumstances may have good intentions, but this may ultimately harm students as it lowers academic expectations. For example, in a study of preservice teachers interning in urban schools, Toshalis (2012) found that, in response to severe underperformance of students, interns would praise students' nonacademic qualities while ignoring the students' need for remediation. In contrast, "hard-caring" teachers hold high expectations coupled with supportive, instrumental relationships that facilitate academic and social development and orient students toward the future (Antrop-González & De Jesús, 2006).…”
Section: Hard Carementioning
confidence: 99%
See 1 more Smart Citation
“…GayStraight Alliances and Safe Space programs are also reliant on the victim/savior construction, because they aim to raise the visibility of caring individuals in schools or other institutions. Despite good intentions, acts of care that rely on deficit or victim discourses to understand LGBTQ students' needs may ultimately do more for the educator than the student because they keep the good educator solidly in the privileged position as she offers compassion to the needy Downloaded by [Stony Brook University] at 07:49 01 July 2015 student (Toshalis, 2011). Educators are able to claim they are doing a good thing (and caring intervention is a good thing), but their visions for creating a safe and supportive school do not include addressing the multiple ways school cultures subtly yet systematically silence and exclude LGBTQ students.…”
Section: Teachers and Carementioning
confidence: 99%
“…This study reveals that educators and institutional policies, either consciously or subconsciously work out of a position of control rather than engagement, though they articulate care and concern for the wellbeing of students. Toshalis (2012) identifies this as a rhetoric of care.…”
Section: A Rhetoric Of Carementioning
confidence: 99%